2020
DOI: 10.1186/s12940-020-00617-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of polybrominated diphenyl ether (PBDE) levels with biomarkers of placental development and disease during mid-gestation

Abstract: Background: Polybrominated diphenyl ether (PBDE) exposures have been associated with adverse pregnancy outcomes. A hypothesized mechanism is via alterations in placental development and function. However, we lack biomarkers that can be used as early indicators of maternal/fetal response to PBDE exposures and/or perturbations in placental development or function. Methods: To evaluate the relationship between PBDE levels and placental biomarkers during mid-gestation of human pregnancy (n = 62), we immunolocalize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…After adjusting for confounders, BDE-207 (OR: 1.10, 95% CI: 1.02-1. 19) and 19PBDEs (OR: 1.01, 95% CI: 1.00-1.02) concentrations in maternal serum were significantly associated with an increased risk of FGR (9). This study also reported an inverse association between PBDEs and placental length, breadth, surface area, indicating that prenatal PBDE exposure may disturb placental growth as the result of reduced placental size (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After adjusting for confounders, BDE-207 (OR: 1.10, 95% CI: 1.02-1. 19) and 19PBDEs (OR: 1.01, 95% CI: 1.00-1.02) concentrations in maternal serum were significantly associated with an increased risk of FGR (9). This study also reported an inverse association between PBDEs and placental length, breadth, surface area, indicating that prenatal PBDE exposure may disturb placental growth as the result of reduced placental size (9).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormones are critical for development of the fetal and neonatal brain, as well as for many other aspects of pregnancy and fetal growth (18). Another possible mechanism may be alterations in placental development and function by epigenetic dysregulation (DNA methylation, histone modifications and microRNAs) and functional and molecular perturbations to human placental (19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, polybrominated diphenyl ether (BDE-47) has been found at the highest level. Varshavsky et al and Kwon et al measured the BDE-47 levels in the placenta and maternal serum during the second trimester of pregnancy, and found that the concentration of BDE-47 was correlated with altered levels of vascular endothelial VE-cadherin, which would affect the invasive ability of trophoblasts [ 67 , 68 ]. In addition, BDE-47 may affect placental function, which was associated with oxidative stress, pro-inflammatory mediators, and decreased monocyte and trophoblast viability [ 67 , 69 ].…”
Section: Role and Mechanism Of Pe Induction By Exogenous Compoundsmentioning
confidence: 99%
“…Varshavsky et al and Kwon et al measured the BDE-47 levels in the placenta and maternal serum during the second trimester of pregnancy, and found that the concentration of BDE-47 was correlated with altered levels of vascular endothelial VE-cadherin, which would affect the invasive ability of trophoblasts [ 67 , 68 ]. In addition, BDE-47 may affect placental function, which was associated with oxidative stress, pro-inflammatory mediators, and decreased monocyte and trophoblast viability [ 67 , 69 ]. Wang et al demonstrated that triphenyl phosphate (TPhP), one of the organophosphate flame retardants, can activate PPARγ in JEG-3 trophoblast cells, interfere with hormone secretion, and induce endoplasmic reticulum stress and cell apoptosis [ 70 ].…”
Section: Role and Mechanism Of Pe Induction By Exogenous Compoundsmentioning
confidence: 99%
“…Previously, we have shown that PBDEs are associated with altered expression of molecules on RNA (Robinson et al, 2019;in vitro) and protein (Varshavsky et al, 2020b; in vivo) levels that are essential for placental development and function. For example, we found that PBDE levels, measured in placenta and maternal sera during mid-gestation, were correlated with altered expression profiles of integrin alpha-1 (ITGA1) and vascular endothelial-cadherin (VE-cadherin or CDH5) in uterine-invading cytotrophoblast (CTB) cells (Varshavsky et al, 2020b). These observations are corroborated by experimental in vitro studies demonstrating BDE-47 to inhibit the ability of primary 2nd trimester human CTBs to migrate and invade (Robinson et al, 2019).…”
mentioning
confidence: 99%